Analysis of the Incidence of the Female Population Omsk Region with Breast Cancer for Ten Years of (2003 - 2012) - N. G. Shirlina; V. L. Stasenko; V. A. Shirinsky (Эпидемиология и вакцинопрофилактика, 2016)
The paper presents the epidemiological characteristics of diseases of the female population of the Omsk region of breast cancer (BC) from 2003 to 2012, Determined the dynamics of morbidity. A comparative analysis of breast cancer incidence rates in urban and rural residents of the area. In the structure of malignant tumors of the female population of the Omsk region the proportion of breast cancer was 23.3% and was lower than the national average (20.0%). In rural areas, compared with the regional center had higher growth rates of incidence of breast cancer (1.5-fold).